Abdominal Aortic Aneurysm - From Basic Research to Clinical Practice 2019
DOI: 10.5772/intechopen.84517
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Progressive Endoleak Type 2 After EVAR

Abstract: An endoleak type 2 (EL2) is a relatively frequent event after an EVAR but 30-35% of EL2 can become progressive, which can cause a loss in the important sealing zone of the stent graft. Diagnosis is made by three-phase CT angiogram or by contrast-enhanced duplex scan. EL2 should be treated if the aortic sac grows more than 5 mm in 6 months time. The first suitable treatment is the endovascular approach with embolization of the inferior mesenteric artery (IMA) or lumbar arteries. Paravertebral puncture, under CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…11 We found that T2ELs occurred in 3 (33%) of 9 patients, equivalent to the incidence of T2ELs previously reported. 9 However, we did not perform contrast-enhanced CT for cases with no enlargement of the aneurysm sac in the last half year after surgery. Therefore, it was difficult to judge whether T2ELs were still persistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 We found that T2ELs occurred in 3 (33%) of 9 patients, equivalent to the incidence of T2ELs previously reported. 9 However, we did not perform contrast-enhanced CT for cases with no enlargement of the aneurysm sac in the last half year after surgery. Therefore, it was difficult to judge whether T2ELs were still persistent.…”
Section: Discussionmentioning
confidence: 99%
“…1 4 Notably, endoleaks are considered a poor prognostic factor, among which T2ELs after EVAR are considered frequent, affecting approximately 25%–30% of patients. 9 Although approximately 80% of patients with T2ELs do not require reintervention, 9 persistent T2ELs have been reported as risk factors for aneurysm sac enlargement and reintervention. 5 Importantly, a previous study found that the risk factors for T2ELs are (1) IMA ≥3.0 mm, (2) LA ≥2.0 mm, and (3) presence of aortoiliac-type aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…In 50% of cases, type II endoleaks are closed independently within a few months; in 10 to 15% of cases they can cause an increase in the diameter of the aneurysmal sac, and in 5 to 10% they can appear in the long-term after surgery. [5][6][7] Modern research data show that 54.2% of type II endoleaks are detected within up to 30 days of observation from the moment of surgery and 39.1% over 30 days, and of these only 8.4% are detected after a year from surgery. 8…”
mentioning
confidence: 99%